Aspectos morfoestruturais do carste em arenitos no nordeste ocidental brasileiro: exemplo da Serra da Capivara e áreas adjacentes (Piauí) - Silva, Mickaelle Braga da (2024)
The present work provides a morphostructural analysis of the development of karst relief in sandstone in the Serra da Capivara (Piauí, Brazil) based on its formation mechanisms, evolutionary stages, and morphological patterns. It examines the karst system’s morphological variables within the context of regional tectonic and structural framework. The studied landscape and adjacent areas are located within the Serra da Capivara National Park (PI), which is recognized nationally and internationally as a prehistoric sanctuary set in the sandstones and Paleozoic conglomerates of the Parnaíba Sedimentary Basin. This area integrates diverse environmental, biological, tourist, cultural, and historical aspects. The site’s exceptional heritage character is closely tied to its archaeological significance, whereas studies on its geological and geomorphological aspects are limited and have received modest scientific attention. In this context, the research aims to analyze the karst relief developed in sandstone within the Serra da Capivara National Park (Piauí, Brazil), to explore the formation conditions, origin, and evolution of the karst relief; to examine the lithostructural and tectonic influences in the area; to demonstrate the relationship between drainage and lineaments in shaping relief morphology; to present the compartmentalization, individualization, and interpretation of karst features within the analyzed system; and to investigate how small- and medium-scale relief forms correlate with larger geomorphological units, assessing whether the processes involved in their formation can provide insights into the region’s landscape history. To achieve these objectives, the following methodologies were employed: bibliographic and cartographic surveys, fieldwork, application of geoprocessing techniques, and data tabulation and analysis. The results highlight the critical role of morphostructural factors in understanding the evolution of the karst relief under study. Analysis of the area’s structural lineaments reveals major lineament trends oriented NE-SW, potentially aligning with the Transbrasiliano lineament. The reactivation of these structures may influence slope orientation and retreat, as well as the direction and incision of primary valleys. Fracturing features, predominantly NW-SE oriented, contribute to valley formation and the confinement of secondary drainage channels within the area. Regarding the origin and evolution of the karst system under study, fracture arrangements associated with bedding planes create conditions for secondary porosity and permeability in the sandstone, facilitating conduits forming into underground galleries. When subjected to erosive processes, these structures manifest as surface canyons, forming rectilinear valleys marked by notable angular connections and the progressive individualization of blocks along the slopes, forming towers, pinnacles, and mesas.